Post-Hierarchical Race: Reconsidering the Nature of Hierarchy within Haslanger's Account of Race - Davidson-Smith, Max (Stance: an international undergraduate philosophy journal, 2021)
In this essay, I consider Sally Haslanger’s social constructivist account of race and propose a modification to the nature of hierarchy specified. According to Haslanger, race will cease to exist post-hierarchy, given that she builds in a requirement of synchronic hierarchy for the existence of race. While Haslanger maintains that racial identity would linger beyond hierarchical treatment in the form of ethnicity, I will suggest this fails to provide adequate conceptual justice for the cultures and aesthetics which emerged out of past oppression. In response, I propose a modification which would allow us to recognize the possibility of post-hierarchical races.